What this is asking is for you to plug values into the following function:[tex]f(x)=\frac{3x-8}{6x}[/tex]
Since the question is asking you to find [tex] f(3)-f(1) [/tex], this is how you work it out:
You take the function;
[tex]f(x)=\frac{3x-8}{6x}[/tex]
And plug the numbers indicated in for x;
[tex]f(x)=\frac{3x-8}{6x}\\
f(3)=\frac{3(3)-8}{6(3)}\\
f(3)=\frac{9-8}{18}\\
f(3)=\frac{1}{18}\\\\
f(1)=\frac{3(1)-8}{6(1)}\\
f(1)=\frac{3-8}{6}\\
f(1)=\frac{-5}{6}\\\\
Now\ what\ you\ do\ is\ you\ subract\ f(3)\ and\ f(1).\\
f(3)-f(1)\\
f(3)-f(1)=\frac{1}{18}-\frac{-5}{6}\\
f(3)-f(1)=\frac{1}{18}-\frac{-15}{18}\\
f(3)-f(1)=\frac{1+15}{18}\\
f(3)-f(1)=\frac{16}{18}=\frac{8}{9}[/tex]
So the answer to f(3) - f(1) = [tex] \frac{8}{9} [/tex]